1976
DOI: 10.1111/j.1526-4610.1976.hed1601024.x
|View full text |Cite
|
Sign up to set email alerts
|

Double Blind Study of Propranolol for Migraine Prophylaxis

Abstract: SYNOPSIS Eighty‐three migraine patients were admitted to a double‐blind, single cross‐over, propranolol vs. placebostudy. Sixty‐two patients completed the trial. The daily dosage was either 80 or 160 mg. propranolol, or an equivalent number of placebo capsules, for 4 to 8 weeks for the first medication and 8 weeks for the second one. At the end of the trial, 32 patients preferred propranolol and 18 placebo. Those who preferred propranolol had greater reduction in severity and frequency of headaches and less c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
0
1

Year Published

1978
1978
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(57 citation statements)
references
References 2 publications
4
52
0
1
Order By: Relevance
“…Throughout my professional career I conducted research, including early studies on the use of propranolol. 39 With Jose Medina, we reported on the efficacy of indomethacin on cluster headache variant. 40 The discovery of propranolol's efficacy in migraine was incidental.…”
Section: United States Of Americamentioning
confidence: 97%
“…Throughout my professional career I conducted research, including early studies on the use of propranolol. 39 With Jose Medina, we reported on the efficacy of indomethacin on cluster headache variant. 40 The discovery of propranolol's efficacy in migraine was incidental.…”
Section: United States Of Americamentioning
confidence: 97%
“…This report prompted numerous clinical trials, with the eventual approval of propranolol for migraine prophylaxis in 1976. Approval was gained on the results of two studies involving 104 patients: Doctor Jose Medina and I reported on 62 evaluable patients [Diamond and Medina, 1976], and an unpublished report of John Graham on 42 cases treated with propranolol. It is amazing that to receive approval from the FDA during our current climate of regulation, evidence must be presented from double-blind studies that enrolled more than 1,000 patients.…”
Section: B-blockersmentioning
confidence: 99%
“…Their use is supported by a good body of evidence from several placebo-controlled trials. [8][9][10][11][12][13] However, they have a disadvantage of significant side effects, such as sedation, decreased blood pressure and, especially in women, weight gain, which can make adherence to treatment a problem for many patients. 14 The success rate for beta-blockers is around 50%, with half of the patients experiencing significant decreases in the number and severity of migraine attacks.…”
Section: Topiramate In Migraine Preventionmentioning
confidence: 99%